2007
DOI: 10.1001/jama.297.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Strategy to Improve Adherence to Tuberculosis Treatment in a Resource-Poor Setting

Abstract: Context Poor adherence to treatment remains a major obstacle to efficient tuberculosis (TB) control in developing countries. Innovative strategies to improve access and adherence to treatment are needed. Objectives To assess the effectiveness of a contextualized intervention strategy aimed at improving patients' adherence to treatment and to evaluate its impact on TB control in a resource-poor country in Africa with prevalent TB infection. Design, Setting, and Patients A cluster randomized controlled trial, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 14 publications
7
115
0
2
Order By: Relevance
“…Our results confirm earlier studies from other program settings showing that household members are good DOT supervisors and can increase adherence and cure rates. 1,10,12,18 Household members appear to be better treatment supervisors than HCW in some program settings since they may more effectively mobilize a network of family support around the patient's treatment than HCW can. The involvement of other household members may be decisive for treatment completion and cure.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm earlier studies from other program settings showing that household members are good DOT supervisors and can increase adherence and cure rates. 1,10,12,18 Household members appear to be better treatment supervisors than HCW in some program settings since they may more effectively mobilize a network of family support around the patient's treatment than HCW can. The involvement of other household members may be decisive for treatment completion and cure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from Senegal 17 is an example of this. This wellcontrolled study reported a 12% higher cure rate among patients allowed to select their own "direct-observation-oftreatment supporter", but also featured intensive and sustained professional supervision and training and monitoring of the supporter at every level of the study.…”
Section: Family Observation Is a Seductive But Risky Conceptmentioning
confidence: 97%
“…In the Senegal study, 17 direct observation of treatment was delivered by a person selected by the patient. Self-administration was not an option.…”
Section: Is There a Place For Family Observation?mentioning
confidence: 99%
“…The retrieval system (phone, letters, home visit, etc.) can bring some patient to the hospital, but it would not be possible to guarantee that they take the prescribed drugs [18,19]. Other method like fixeddose combination may not prevent defaults.…”
Section: Discussionmentioning
confidence: 99%